Tourism and Leisure 2014
DOI: 10.1007/978-3-658-06660-4_11
|View full text |Cite
|
Sign up to set email alerts
|

Applying Business Intelligence for Knowledge Generation in Tourism Destinations – A Case Study from Sweden

Abstract: The book chapter at hand presents a knowledge infrastructure recently implemented as genuine novelty at the leading Swedish tourism destination, Åre. By applying a Business Intelligence (BI) approach, the Destination Management Information System Åre (DMIS-Åre) drives knowledge creation and application as a precondition for organizational learning at tourism destinations. Schianetz et al. 's (2007) concept of the 'Learning Tourism Destination' and the 'Knowledge Destination Framework ) build the theoretical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Fuchs et al, (2014) have concluded that Big Data tools can provide real-time knowledge on how tourists are behaving in the online environment in relation with a destination. This means that the Big Data tools can provide knowledge which will help the destination's decision makers to better understand what the expectations are and needs of potential tourists of a destination, while the same outcome was noted from Fuchs et al, (2015).…”
Section: The Current Trends On Big Data In the Tourist Industrymentioning
confidence: 92%
See 1 more Smart Citation
“…Fuchs et al, (2014) have concluded that Big Data tools can provide real-time knowledge on how tourists are behaving in the online environment in relation with a destination. This means that the Big Data tools can provide knowledge which will help the destination's decision makers to better understand what the expectations are and needs of potential tourists of a destination, while the same outcome was noted from Fuchs et al, (2015).…”
Section: The Current Trends On Big Data In the Tourist Industrymentioning
confidence: 92%
“…Overall, Big Data can have a major contribution as a tool which will provide the necessary data for taking critical decisions. The trend is that Big Data analytics can be used as a knowledge creation tool and the use of business intelligence approaches (Fuchs et al, 2014(Fuchs et al, , 2015Marine-Roig & Clav, 2015;Höpken et al, 2015), or for the creation of databases Stylos et al, 2021). The most important trend, however, is that Big Data Analytics can become a useful strategic tool (Varelas et al, 2020;Miah et al, 2017;Li et al, 2018;Li et al, 2020).…”
Section: The Current Trends On Big Data In the Tourist Industrymentioning
confidence: 99%
“…The system obtains knowledge from tourist destination indicators that measure destination performance and tourist experience, gaining new knowledge from the customer-based destination process. Further research development was carried out with the Åre Destination Management Information System (DMIS-Åre) [27], aimed at studying tourist habits. Research using BI tools integrated with tourism destinations, web monitors, web mining, and web analytics aims [28], to determine tourist habits.…”
Section: Related Workmentioning
confidence: 99%
“…Obviously, this development is of particular interest to HSN, since it offers a route to provide lifelong learning support to a large sector of the industry and links in to the formal qualification system they provide. Work in this area has already been undertaken in agriculture in New Zealand [54] and in tourism in Sweden [55], but the approach taken in this project is novel, focusing on the development of the dashboard as a virtual learning environment.…”
Section: B Integrating With the Sakai Vlementioning
confidence: 99%